A COMPARATIVE STUDY ON THE EFFECT OF TWO INDIGENOUS AYURVEDIC FORMULATIONS ON LACTATION (International Journal of Ayurveda and Pharma Research, 2018)
A clinical trial was conducted to compare the lactogenic properties of two indigenous formulations, the trial drug mentioned in Arogyakalpadrumam and control drug- some selected drugs from Chikithsamanjari, the efficacy of which was already proved. The study was carried out in the outpatient section of the Department of Prasuthi and Sthreeroga, Govt. Ayurveda college Hospital for women and children, Poojappura, Thiruvananthapuram during 2013-2014. Lactating mothers, complaining of reduced breast milk even after 2 weeks from delivery were screened and grouped into two groups each containing of 15 patients. Data were collected by interviewing mothers using a pre-structured questionnaire with a scoring system. Study drug and control drug are given to each group, in a dose of 6gm powder with 24ml milk twice daily 1hr before food for three months. Evaluations of all the parameters were done at an interval of 30 days in each group. Differences in the score values were noted. Assessment of growth and development of children using Anthropometric parameters and CDC chart were recorded. The data were analyzed using the most appropriate statistical tests. Significant changes were obtained in the clinical parameters in the study group used for assessment such as number of feeds per day, interval between feeling of fullness of breasts, duration of feeds, sleep habits of the baby. There was no statistical significance in increasing number of feeds during night time in both groups. Both drugs have lactogenic properties. All children in both groups attained their natural growth and development. There was a small statistical significance in increasing birth weight in study group when compared with the control group. In the study group poor and moderate response was 0% while in control group they were 13.3%. Good response in the study group was 86.7% while it in the control group was 60.1%. There was a very good response in both groups which was 13.3%.